Blood in the mythological thought of the Eastern Slavs (On the material of medical conspiracy) - Temchenko, A. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. In the context of Indo-European mythology interesting is the theme of blood ritual which was practiced by the ancient Slavs. Most often research is limited to the symbolism of blood in ritual sacrifice. However, it remains understudied topic of the semantics of blood from the mythology of the treatment. Purpose is to study the problematic aspects associated with the semantics of blood in the medical texts of the population in Ukrainian and Belarusian Polisia: semiotic design, built on the principle of binary semantic oppositions. Results. In mythological thought of the Slavs blood is seen as a substance that nourishes a living body, therefore, in medical texts it acquires polar characteristics – its lack causes disease / death, but its excess is also harmful. Clear sign of conspiracy from the bleeding is the actual lack of abstract concepts that represent the blood that indicates the origin of archaic texts. But «quality» blood is labeled with specific values in a particular color, touch and taste. The origin of the opposition («black / red», «cold / hot», «static / movable», «sweet / bad»), parts of which indicate different state of the blood. Opposition relations form of system coordinating values where red, hot, moving, sweet provoke the creation of semantic branching, which determine the degree of its vitality. The most powerful, from the point of view of the ritual acts of ardent blood that borders on other concepts with the root, which denote natural power. In society it refers to government officials and military aristocracy (Yaroslav, Yaropolk, Jaromir); in traditional beliefs – the status of mythological creatures. Blood is an integral part of the mythological title that is associated with the idea of life, therefore, in medical texts it does not apply to representatives of the other world. The redundancy of «awesome power» that harm caused by ritual, so the «blood» (excessive force) produced, which explains the mythological subtext. In other words, the movement of blood through the arteries (the body) is matched with stream (the universe), powerful which destroys the shore, resulting in extra blood, causing a «rage», taken out of the body. The image of the ardent blood differs from similar in meaning fierce blood / harmful / poisonous. The ideological basis of these beliefs is the identification of natural and bodily moisture. Excessive rains, prolonged flooding are mapped to the «extra» blood. In this regard, there was ritual, the rules of its release (phlebotomy) because it threatened the universal outflow of blood is a natural moisture and cause general dehydration / drought. Associative mapping of natural bodily moisture and explaining why in the text of the myth is embedded the image of the sacred rivers (the Jordan) which is a kind of standard of flow of all water / natural and black / Nude year. Drought is associated with lack of blood and Vice versa, so during fever / heat, leading to drying of the body of the patient to humidify / wiping dew. According to whipping dew (intentional breakfast) could lead to destruction of crops / livestock and was a threat to the health and life of the owner of the field (in the customary law of magical manipulation with dew was considered a crime). Reverse action is «hydration» of the earth «body dew» – by the blood of the sacrifice. For example, in the Kiev Rus on the eve of the Perun`s day is sacrificed with an unmarried guy and a girl. Similar is lyrics from bleeding. To stop the leakage of life-giving moisture «beat» the dam or turned to sand and stone objects, which were associated with absolute dryness. Their magical use of dualist rite, because it is a threat to natural / bodily moisture. Similar is the appeal to the supernatural (bloodless) / melotronic creatures – sheep / the crippled, the naming of which can provoke their appearance (goes well with the mythological semantics of the so-called husband). The absolute concentration of dry stone and sand operated by the rite, when it is necessary to dry until the end of something too wet. For example, slugs and snakes (Association of excess moisture) is sent under a rock, which crushed also things the patient, thereby simulating the burial customs of the unclean dead. In other words, the stone designs of your dry items that are matched with him: the liquid blood turns into solid, living person – a dead man. Conclusion. The image of blood concentrating the meaning for the symbols of life that leads to the formation of the opposition ties: red / black, hot / cold, sweet / bitter, fast / slow, spring / February, so the symbolism of blood associated key cultural concepts associated with the concept of force.